2012
DOI: 10.1055/s-0038-1639446
|View full text |Cite
|
Sign up to set email alerts
|

Emerging eHealth Directions in the Philippines

Abstract: SummaryObjectives: This paper aims to provide an overview of research and education initiatives in the Philippines. Moreover, it outlines the various agencies and organizations that spearhead the eHealth projects. Methods: The researchers utilized internet-based review of literature, key informant interviews and proceedings from two eHealth conferences among Filipino researchers in 2011 organized by the authors. Results: eHealth capacities in the areas of research, education and service have progressed dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…In line with the Philippine e-Health Systems and Services Act, feasibility and cost-effectiveness studies should be done prior to implementation of telehealth-related programs in healthcare facilities (53). In addition, awareness campaigns, workforce training, capacity-building, and policy-updating are also important measures to ensure sustainable programs (23,32). In relation to local telerehabilitation experience, however, these crucial steps were bypassed during the COVID-19 pandemic to urgently come up with interim guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the Philippine e-Health Systems and Services Act, feasibility and cost-effectiveness studies should be done prior to implementation of telehealth-related programs in healthcare facilities (53). In addition, awareness campaigns, workforce training, capacity-building, and policy-updating are also important measures to ensure sustainable programs (23,32). In relation to local telerehabilitation experience, however, these crucial steps were bypassed during the COVID-19 pandemic to urgently come up with interim guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated or attempted to address the lack of awareness and acceptance of telemedicine among stakeholders. Research fora, stakeholders' meetings, campaigns, and conferences conducted by Fernandez-Marcelo et al in 2012 stimulated awareness of telehealth in a wider scale locally (32). The National Telehealth Service Program of the Department of Health was an important milestone in spreading telehealth awareness in rural areas, as shown by Macrohon and Cristobal (30,33) and Gavino et al (37).…”
Section: Challenges To Telerehabilitationmentioning
confidence: 98%
See 2 more Smart Citations
“…Only one study was identified suggesting low demand for teleophthalmology. 8 Types of diseases applied in the teleophthalmology studies are as shown in Table 1. Most studies focus on diabetic retinopathy (DR) of which application pattern is quite consistent with the conventional clinical method.…”
Section: An Overview Of Teleophthalmology Programs Currently Deployedmentioning
confidence: 99%